Response to Britz (2022) regarding the validity of the giant sunfish Mola alexandrini (Ranzani, 1834) (Teleostei: Molidae) - Sawai, Etsuro; Nyegaard, Marianne (Zootaxa, 2023)
The small family of ocean sunfishes has a long and complicated taxonomic and nomenclatorial history dating back several centuries. Most recently, Britz (2022) questioned the validity of Mola alexandrini (Ranzani, 1839) as the valid name for Mola sp. A sensu Yoshita et al. (2009). Specifically, he questioned the authenticity of the purported Orthragoriscus alexandrini holotype rediscovered by Sawai et al. (2018) due to uncertainties regarding the original units of measurement, along with discrepancies between the original illustration and the purported holotype. He also questioned the reliability of the illustration to reflect the fresh morphology, and the adequacy of the species description (sans illustration and holotype) to link it to any of the currently recognized Mola species. In summary, Britz (2022) opined that M. alexandrini is a species inquirenda. Here we respond to Britz’s concerns with the findings from an additional literature review. Firstly, the original species description appears to give measurements in ‘Parisian units’, yielding a discrepancy in length with the purported holotype within human error. However, due to various uncertainties, length does not appear to be a robust piece of evidence to neither confirm nor refute the specimen’s authenticity. Secondly, the morphological differences between the original illustration and the purported holotype were found to be within the expected level of accuracy for Mola illustrations at the time, by both Ranzani and others. Thirdly, a contemporaneous publication describes how Ranzani himself bought the specimen which became the Or. alexandrini holotype, suggesting he would likely have seen it in its fresh state, rendering it unlikely he would have produced a species description and illustration incongruent with this. Fourthly, re-examining the original species description suggests this provides adequate and sufficient information to link Or. alexandrini to Mola sp. A, even in the absence of a holotype. Finally, during this review, we came upon an even older paper describing Or. alexandrini, and we conclude that the currently valid name for Mola sp. A sensu Yoshita et al. (2009) is Mola alexandrini (Ranzani, 1834).